DNS blocking in VN: bbc.com, facebook.com, google.com, instagram.com, medium.com +13 more (Vietnam) - Voidly (2026)
CRITICAL severity censorship detected in Vietnam. Confidence: 85%. Data sourced from CensoredPlanet.
Censorship Incident ID: VN-2026-0004
Keywords: censorship; VN; censorship; critical